The Effect of Project Based Learning Model on the Students Questioning Ability - Komalasari, Baiq Resti; Setiadi, Dadi; Kusuma, ASHM; Jufri, A. Wahab (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
The questioning ability is the foundation for building students' thinking skills in finding solutions to problems. This study aimed to determine the effect of the project-based learning model on the ability to ask questions of biology students in class X SMAN 7 Mataram. Quasi-experimental method and Nonrandomized Control Group Design were used in this study with a quantitative approach. The population of this study was class X SMAN 7 Mataram, and random sampling was used as a sampling technique so that four classes were obtained as samples with details of class XG and XF as the experimental group while XK and XL as the control group. The instrument used is Questioning Skills. Data collection of students' questioning skills is done by making five questions, then analyzed by anacova (analysis of covariance) at the 5% significance level using the SPSS 21 program. The results of hypothesis testing in this study show an effect of the project-based learning model on the ability to ask biology students in class X SMAN 7 Mataram.